Hepatectomy increases metastatic graft and growth in an immunocompetent murine model of peritoneal metastases. Issue 6 (June 2018) - Lo Dico, Rea; Tijeras-Raballand, Annemilai; Bonnin, Philippe; Launay, Jean Marie; Kaci, Rachid; Pimpie, Cynthia; Malgras, Brice; Dohan, Anthony; Lo Dico, Gianluigi Maria; Pocard, Marc
Abstract: Background: Curative surgery of synchronous peritoneal metastases (PM) and colorectal liver metastases (LM) has been recently investigated as feasible option. When synchronous peritoneal and liver resection is not achievable, the sequence of the surgery remains unknown. Our hypothesis was that liver resection (LR) promotes peritoneal growth resulting in a non-resectable PM. We sought to analyse the effects of major LR and liver regeneration after hepatectomy in a murine model of PM and the associated angiogenesis. Methods: Murine model of colorectal PM in Balb/C mice was developed by intraperitoneal injection of different CT-26 tumour cell concentrations. Five days after the injection, mice were randomized into three groups: 68% hepatectomy group, sham laparotomy and control group without surgery. On post-operative days 1, 5 and 20, PM was evaluated macroscopically, tumour growth and liver regeneration by immunohistochemistry, and angiogenesis by immunofluorescence. Circulating progenitor cells, plasmatic cytokines and digestive arterial blood flow velocity measurements were also analysed. Results: Reproducible murine model of limited colorectal PM was obtained. Surgery induced PM increases and promoted neo-angiogenesis. Major hepatectomy influence the tumour growth in the late phase after surgery, the extent of extra-peritoneal metastasis and the increase of Ki-67 expression in the remnant liver. Conclusions: This animal model confirms the pro-tumoural and pro-angiogenic role of surgery, laparotomy and major LR, which promotes the increase of angiogenic factors and their participation in PM growth. These results suggest that peritoneal resection should be first step in the case of two-step liver and peritoneal surgery for patients with colorectal PM and LM.